PRODUCTION OF TRANS-RESVERATROL IN CALLUS TISSUE OF ÖKÜZGÖZÜ (VITIS VINIFERA L.) IN RESPONSE TO ULTRAVIOLET-C IRRADIATION - N. Keskin; B. Kunter (Journal of Animal and Plant Sciences, 2010)
In this study, the effects of ultraviolet (UV) irradiation time, incubation time and callus age were investigated for trans-resveratrol induction in callus cultures of Vitis vinifera L. cv. Öküzgözü. Callus tissues were exposed to 254 nm UV light at 10 cm distance from the source for 10 and 15 minutes by opening covers of the petri dishes in a sterile cabinet. High Pressure Liquid Chromatography was used for determining trans-resveratrol production and concentrations were recorded at 0, 24, 48 and 72 hours after beginning of incubation. The highest trans-resveratrol concentration (62.23 g/g callus fresh weight) was determined at 48 hours of 12 -day-old callus cultures irradiated for 15 min. 15 min UV irradiation period was found to be effective for induction of trans-resveratrol production and thus callus cultures could be convenient for trans-resveratrol production.
Keywords: Öküzgözü (Vitis vinifera L. cv.); trans-resveratrol; callus culture; UV irradiation